Why most African states may be at war with each other in 2063 - Francis Onditi; Shadrack Mulei Kithiia (The Thinker)
The year 2063 is important to the AU and the African people. Aside from the fact that, by then, many African states will be celebrating 100 years’ independence, this is also the year that the goals listed in the Agenda 2063 should have been achieved. The Agenda 2063, which was created in 2015, groups its objectives into four broad categories: inclusive growth; integration; governance; security; cultural identity; women and youth; and partnership